TikTok and Hijab: Questioning Islamic Values in Digital Sphere - Soedardi, Riza Adrian (SHAHIH: Journal of Islamicate Multidisciplinary, 2020)
TikTok as a new social media provides many features for users to self-generate content expressively. In its platform, most of users producing dancing content excessively and some of the users are women who wear hijab. This article will examine the concept of hijab and hijab women in digital sphere like TikTok. The method of this article utilizes qualitative and it also take library research for looking some theories of hijab and digital sphere phenomena. The result shows that many Muslim scholars consider that dancing is allowed in four condition, which are no alcohol, no gender mix, no effeminate moves, and not to do it excessively. By those condition, this article invites Muslim scholars to question the phenomena on digital sphere.